Salicylate toxicity model of tinnitus - Stolzberg, Daniel; Salvi, Richard J.; Allman, Brian L. (Frontiers in Systems Neuroscience, 2012)
Salicylate, the active component of the common drug aspirin, has mild analgesic, antipyretic, and anti-inflammatory effects at moderate doses. At higher doses, however, salicylate temporarily induces moderate hearing loss and the perception of a high-pitch ringing in humans and animals. This phantom perception of sound known as tinnitus is qualitatively similar to the persistent subjective tinnitus induced by high-level noise exposure, ototoxic drugs or aging which affects ~14% of the general population. For over a quarter century, auditory scientists have used the salicylate toxicity model to investigate candidate biochemical and neurophysiological mechanisms underlying phantom sound perception. In this review, we summarize some of the intriguing biochemical and physiological effects associated with salicylate-induced tinnitus, some of which occur in the periphery and others in the central nervous system. The relevance and general utility of the salicylate toxicity model in understanding phantom sound perception in general are discussed.